Comparison of Snail-1 and Estrogen Receptor Immunoexpression between Fibroadenomas and Phyllodes Tumors - Quzwain, Fairuz (Fakultas Kedokteran Universitas Brawijaya, 2020)
Fibroadenomas (FA) and phyllodes tumors (PT) are fibroepithelial lesions in the breast, which until now the relationship between the pathogenesis of both have not been ascertained yet. Epithelial cells are thought to be involved in the regulation of changes in the stromal cells in the PT, so it can be estimated that this process is involved in epithelial-mesenchymal transition (EMT). This study aims to compare of snail family transcriptional repressor 1 (Snail-1) and estrogen receptor (ER) impression as EMT factors among tumor typeÂ (FA, benign PT, boderline PT and malignant PT). This study was an observational analysis with the cross-sectional method. After the histologic grade of the samples was reviewed, immunohistochemistry examination for ER and Snail-1 was performed. Statistical analysis for categorical data was tested by chi-square test. There were 66 samples, consists of 20 FA, 17 benign PT, 16 borderlines PT, and 13 malignant PT. A significant difference in the loss of ER expression in borderline and malignant PT was found compared to FA and benign PT. This is inversely proportional to the snail-1 expression, where the expression was high in borderline PT and malignant PT stromal cells. This could support the consideration of the pathomechanism regulation of epithelial-mesenchymal cell transition changes in FA with PT, where Snail-1 is one of the proteins in the regulation of the EMT and RE processes acting as an inhibiting factor in transcription factors in the mechanism of EMT occurrence.